logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
Home  >>  CBSE XI  >>  Math  >>  Sequences and Series
0 votes

If the sum of $n,2n\:and\:3n$ terms of an A.P. are $S_1,S_2\:and\:S_3$ respectively, then show that $S_3=3(S_2-S_1)$

Can you answer this question?
 
 

1 Answer

0 votes
Toolbox:
  • Sum of $n$ terms of an A.P $=\large\frac{n}{2}$$(2a+(n-1)d)$
Given that $S_1=$ Sum of $n$ terms $=\large\frac{n}{2}$$(2a+(n-1)d)$
$S_2=$Sum of $2n$ terms $=\large\frac{2n}{2}$$(2a+(2n-1)d)$ and
$S_3=$ Sum of $3n$ terms $=\large\frac{3n}{2}$$(2a+(3n-1)d)$ of an A.P.
$\Rightarrow\:S_2-S_1= \big[\large\frac{2n}{2}$$(2a+(2n-1)d)\big]- \big[\large\frac{n}{2}$$(2a+(n-1)d)\big]$
$\qquad\:=\large\frac{n}{2}$$\big[(4a-2a)+(4n-2-n+1)d\big]$
$\qquad\:=\large\frac{n}{2}$$\big[2a+(3n-1)d\big]$
$3(S_2-S_1)=3\large\frac{n}{2}$$\big[2a+(3n-1)d\big]=S_3$
Hence proved.
answered Mar 28, 2014 by rvidyagovindarajan_1
 

Related questions

Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...